Engineering Grand Challenges in Scholar Programs - Amouzad Mahdiraji, Ghafour; Chung, Edwin C.Y; Namasivayam, Satesh Narayana; Hosseini Fouladi, Mohammad (Springer Nature Singapore : Imprint: Springer, 2019)
This book explains how Taylor's University implemented a curriculum in their engineering program that prepares students to address challenges facing the world. Aim is to enable Engineers put their knowledge into application to meet the 14 challenges of the century as outlined by the National Academy of Engineering (NAE) of the United States. The research groups are organized around the 14 grand challenges for engineering The structure of their syllabi is organized in a way that they address the 5 core competencies: Research Experience, Entrepreneurship, Service Learning, Interdisciplinary Curriculum, Global Dimension. It uses the CDIO educational framework, a project-based learning approach that provides students with the big picture of engineering. Through this method, students are able to: Master a deeper working knowledge of the fundamentals of engineering Lead in the creation and operation of new products and systems Understand the importance and strategic value of research work As the only programe of its kind outside North America, it offers the brightest minds the opportunity to face real-world issues and places them on the cutting edge of the engineering world.